Modesto Bargalló in Spain (1894-1939): A biography between the history of education and the history of science - Moreno Martínez, Luis (Historia y Memoria de la Educación, 2020)
This paper deals with the professional career of Modesto Bargalló Ardévol (1894-1981) in Spain, who has been singled out as a one of the outstanding renovators of Spanish science teaching in the first third of the 20th century. After undertaking a review of the biographical studies of this training- school professor and an analysis of his wide range of publications and other historical sources, the paper focuses on several neglected questions regarding his work in Spain. I will argue that Modesto Bargalló’s biography can contribute to a reflection on the use of teacher biographies for exploring the history of science education and its role as a field of scholarship shared by historians of education and science historians.